Media Sosial untuk Pembelajaran Bahasa Arab pada Masa Pandemi: Kajian Kualitatif Penggunaan WhatsApp pada Sekolah Dasar di Indonesia - Meidiana Sahara Riqza; M Muassomah (Alsina : Journal of Arabic Studies, 2020)
Learning in the era of 5.0 society has experienced rapid mediation, especially in educational program. Teachers began to innovate using various media, especially using WhatsApp in learning Arabic Language. Arabic language has been considered a very difficult and tedious subject for islamic elementary school children. Efforts and high creative power continue to be done to foster fun learning of Arabic language. The purpose of this study besides want to see how the process and application of WhatsApp social media in learning Arabic language is also to increase knowledge and insight for Arabic teachers in utilizing the development of technology and information at the islamic elementary school level. This research method uses qualitative research by using descriptive analysis. Data collection techniques in this study using observations, interviews, and document notes. The results of this research concluded that WhatsApp social media can facilitate learning and long distance communication between teachers and students when they are in a pandemic, create fun learning, train students' independence, and also have more values, an environmentally friendly. This research suggests that there is more supervision of students in applying WhatsApp social media to learning Arabic language at the islamic elementary school level.